Answer:
Option b. (x = 3, y = 20, z = -14)
Explanation:
Given:
2x + 2y + 3z = 4
5x + 3y + 5z = 5
3x + 4y + 6z = 5
Solve using Cramer’s rule
∴
![\left[\begin{array}{ccc}2&2&3\\5&3&5\\3&4&6\end{array}\right] =\left[\begin{array}{ccc}4\\5\\5\end{array}\right]](https://img.qammunity.org/2021/formulas/mathematics/high-school/hdfowwtqo9ae4edg28gz887em4lo8fhc4y.png)
∴A =
![\left[\begin{array}{ccc}2&2&3\\5&3&5\\3&4&6\end{array}\right] = -1](https://img.qammunity.org/2021/formulas/mathematics/high-school/82h4knf25mwz6n43da05kqfd0w8qxt004t.png)
Ax =
![\left[\begin{array}{ccc}4&2&3\\5&3&5\\5&4&6\end{array}\right] = -3](https://img.qammunity.org/2021/formulas/mathematics/high-school/7vxr1clq6jmr31dbweux0qzzi1ks2xzxhp.png)
Ay =
![\left[\begin{array}{ccc}2&4&3\\5&5&5\\3&5&6\end{array}\right] =-20\\](https://img.qammunity.org/2021/formulas/mathematics/high-school/16l8pxivpkhavce310jov0gewz3f8k2o9t.png)
Az =
![\left[\begin{array}{ccc}2&2&4\\5&3&5\\3&4&5\end{array}\right] = 14](https://img.qammunity.org/2021/formulas/mathematics/high-school/dyc4ixz0k6oyfs04s15s074oj6l6yi2xmg.png)
∴ x = Ax/A = -3/-1 = 3
y = Ay/A = -20/-1 = 20
z = Az/A = 14/-1 = -14
So, the answer is option b. (x = 3, y = 20, z = -14)